Readiness of the national textile industry in facing trade liberalization - Tjia Chen Ming (Digital Business: Tren Bisnis Masa Depan, 2022)
This study found that there are three alternative strategies, namely: strength-opportunity, weakness-opportunity, weakness-threats. The support needed by the business world from the government is: R & D development, information on market opportunities, ease of export, sources of funds other than the banking industry to carry out machine restructuring. The textile industry on the world stage is no longer a new figure but an old face. The term textile that we usually hear comes from the Latin word "texere" which means to weave. Textile is a commodity that has wide usage. Most of the output from the textile industry by the community is used to meet clothing needs. However, apart from being used for clothing, textiles can also be used for other things, such as medicine, the car industry. The car industry uses textile products in the form of upholstery covers. Textile products used in the medical world include: surgical threads, bandages. How a country takes advantage of the new, overcomes the challenges that arise depending on the strengths & weaknesses inherent in the respective national textile industries. This study aims to describe what strategies can be carried out by the national textile industry to obtain maximum benefits from the elimination of textile export quotas. The research data will be analyzed using the SWOT analysis method.